Derechos del alimentante ante la falta de citación con la demanda de pensión alimenticia y la acumulación de la pensión, en el Cantón Guaranda, 2022. - Arteaga Guamán, Ruperto Mesías (2024)
The summons with the complaint is a transcendental procedural act, which informs the defendant of the content of the complaint and the provisions imposed on it, in such a way that the defendant can exercise his legitimate right to defense with full knowledge of what the plaintiff demands. In the case of alimony, this is instituted in order to provide the beneficiary of alimony with the necessary means to meet his needs. This pension is provided according to the economic possibilities of the obligor, according to the pension table. minimal. In the case of maintenance proceedings, and their incidents, at the time of qualifying the claim the judge sets a provisional pension, as ordered by the General Organic Code of Processes and after its execution, the defendant obligor must be summoned in order to that the procedural dynamics, of the summary procedure, continue, and in the single hearing the final pension is set. However, the very common situation occurs that, at the time of filing the claim for maintenance, once qualified, the plaintiff does not summon the defendant, leaving the process paralyzed, and generating a constant accumulation of provisional alimony to the detriment of the rights of the defendant alimony, since this accumulated pension, when the single hearing is held, will be ordered to be liquidated and paid. 3 This action is detrimental to the rights of the obligor, since it is subject to the discretion of the acting party to be summoned when it pleases, accumulating a provisional alimony that must be paid with their respective interests, even with this objective the constant enforcement measures in the General Organic Code of Processes. Keywords: Summons, food process, accumulation of alimony.